Redescription of Chilenoperla puerilis (Gripopterygidae: Plecoptera) from the eastern Andes of Patagonia - Pessacq, Pablo (Zootaxa, 2016)
The male and the last instar larva of Chilenoperla puerilis Illies (Gripopterygidae) are redescribed from Chubut Province, Argentinean Patagonia. Wing venation previously not described, differs from other described species in the genus. The larva is separable from that of C. elongata Vera and C. puelche Vera. Comments on the generic and specific position of the material studied and similarities and differences among the genera Chilenoperla Illies and Pelurgoperla Illies are included. Until new systematic and phylogenetic evidence becomes available no taxonomic changes are proposed.